Peningkatan Kemampuan Pelatih Lari Sprint Jarak Pendek Melalui Kepelatihan Program Latihan - Sutoro Sutoro (University of Cenderawasih, 2013)
Abstract : Development of Skills to Trainer of the sprinter through the program of TOT. The study of application is aiming for trainers and athletes of sprinter to apply a variety of techniques as training models in the movements feet and arms. And also to have the ability to lead and apply Sport Science and Technology. The study used methods of class Action with the approach of 2 cycles. The procedure consists of: (1) Action plan, (2) Application of action, (3) Observation and evaluation, (4) Analysis and reflection. The techniques and data gained from: interviews, questioners and observation. The results from action 1 (cycle 1) can be concluded as follow: Two of trainers (28%) could be able to submit and apply the techniques of training models, the movements of the feet, legs, arms and hands and also Sports Science and Technology. Four trainers (59%) could be able to submit and could not practice the training program yet. Five of trainers (70%) failed to use the techniques of training models and the techniques to move feet/legs, arms and hands also Sports Science and Technology. Later on the second cycles it is concluded that: All of trainers (100%) could be able to submit and practice the techniques to move feet/legs, arms/hands and also Sports Science and Technology. Suggestions: The study of this Sports Action should be continued in order to improve the skill of the athletes. How to use the study of Sports Action to promote and popularize the numbers of athletic sports.Keys: The skill to train 100 m, 200 m and 400 m.